Utilizing Facebook Marketplace to support PKK groups in Ngoro Village, Ngoro District, Jombang Regency - Utami, Budi (Universitas PGRI Semarang, 2025)
Through training, this community service project seeks to introduce and develop a hydroponic plant system in Ngoro Village. The potential of Ngoro Village, especially the enthusiasm of the PKK group for the initiative to empower hydroponic plants, is the motivation. The fact that every household has limited land makes hydroponic gardening very important. This exercise utilizes training and socialization techniques. The aim of the outreach is to provide information about hydroponics, and the aim of the training is to practice growing green lettuce and other hydroponic plants. The success of this activity is evaluated using previously established metrics. Generally, sixty percent of those who receive invitations come to this activity. From the beginning of the material to the practicum, participants showed high enthusiasm. Thanks to this training, the residents of Ngoro Village can immediately start growing hydroponically.